Mobilising Transnational Expertise in National Construction: Exiled Academics and the Transformation of Interwar Turkey - Dogan, Aykiz (Serendipities. Journal for the Sociology and History of the Social Sciences, 2026)
This article examines transnational expertise in state formation, focusing on early Republican Turkey’s strategic mobilisation of foreign specialists, particularly European academics fleeing Nazism. These exiled scientists were invited with high aspirations for international expertise, unburdened by foreign influence, and provided with arrangements to act as modernising agents. This study analyses their contributions to Turkey’s development, the challenges of their integration, and the political choices that empowered or marginalised scientists. It reveals how efforts to avoid reliance on a single foreign model inadvertently fostered new dependencies. The article highlights the unequal dynamics of North-South scientific circulations and challenges assumptions about the novelty and neutrality of science-driven governance.